Geographische Beobachtungen auf einer Forschungsreise in Chile - Weischet, Wolfgang (ERDKUNDE, 1959)
In addition to the general conclusions drawn from specific investigations, this report communicates the results of geomorphological and climatological observations between Chiloë and the Little North. With regard to the Llaima volcano, observations on its orography, the boundaries of its vegetation zones, its snow lines and solifluction phenomena are reported. By means of sketch maps the geomorphology of the Valdivia mountain region is characterized and an attempt is made to divide on a geomorphological basis the de los Lagos region into its natural units. Observations on the Osorno and Calbuco mountains resulted in establishing the present climatic snowline at 1900 m., i. e. 300 m. higher than the value usually quoted. Measurements of the inclination of trees and observations of the gradual decline of tree crown deformation from Chiloe to the Rio Laja are compared with the frequency diagrams of wind directions at the meteorological stations and are used, together with other climatological, geomorphological, hydrological and human-geographical facts to discuss the location of the southern boundary of the sub-tropics in Chile. Finally, this report contains observations of terraces and raised beaches in the Little North. In a table the latter are compared with the altitudes of raised beaches, as quoted in publications, for other parts of South America, as well as North America and Europe. The author wishes to thank his Chilean hosts for their kind reception and always forthcoming assistance.